ChemInform Abstract: Development of Intramolecular Vicinal Diamination of Alkenes: From Palladium to Bromine Catalysis. Issue 26 (6th June 2013) - Muniz, Kilian; Martinez, Claudio
Abstract Review: 67 refs.